Pengentasan Kemiskinan Melalui Metode Spasial Perkotaan Dalam Pengembangan Sustainable Development Goals (SDGs) Kota Surakarta - Ridayanti, Ainuun; Nugroho, Asianto; Candrakirana, Rosita (Peneliti.net, 2024)
Poverty is a major and underlying problem in Indonesia. Poverty is usually caused by education, income, location, health care, finances and public services. One of the processing operations is city area processing. Through a complete and independent understanding in a structured program. The Sustainable Development Goals (SDGs) state that poverty is a priority issue that needs to be addressed urgently. Solving poverty is closely linked to global goals such as clean water, sanitation, well-being and health. Poverty is also a major problem in the city of Surakarta, which is currently developing aggressively and focusing on urban spatial planning. Because the study is descriptive and qualitative, the information obtained is in the form of verbal information. As outlined in the National Long-term Development Plan (RPJN) 2005-2025 and the Regional Medium-term Plan 2021-2026 (RPJMD), developing a poverty reduction strategy is an important step in influencing sustainability. The purpose of this study is to examine urban, riverside, and suburban poverty mapping. A phenomenological approach is used to acquire primary and secondary data sources. The method of collecting data by studying the literature on documents is deductive analysis using deductive methods. The results of this study show that there are differences in urban and regional poverty rates, but they share the same indicators. Based on the information obtained, practical solutions can be implemented. Specifically, the orderly structure of settlements, the coping with unexpected disasters, the provision of sanitation services, the coping with waste pollution, the activation of natural resources (SDA), and the certification of workers in the formal sector. Increase.